PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (STUDI KASUS MAHASISWA AKUNTANSI UNIVERSITAS MATARAM) - PUTRI BIMA WATI; LUKMAN EFFENDY (GANEC SWARA, 2024)
This study aims to determine the effect of emotional intelligence, spiritual intelligence, and learning behavior on the understanding of accounting students at Mataram University. The research method used in this research is a survey method with the form of written questions through a questionnaire as many as 249 students as samples in this study. Data analysis using Partial Least Square (PLS) technique through SmartPLS 3.0 software application. The results showed that emotional intelligence has no effect on accounting understanding because the ability to understand accounting while studying does not always depend on self-control, social skills, but spiritual intelligence has a significant effect on accounting understanding, and learning behavior has an effect on accounting understanding